Methods for Streamlining Intervention Fidelity Checklists: An Example from the Chronic Disease Self-Management Program - Ahn, SangNam; Smith, Matthew Lee; Altpeter, Mary; Belza, Basia; Post, Lindsey; Ory, Marcia G. (Frontiers in Public Health, 2015)
Maintaining intervention fidelity should be part of any programmatic quality assurance (QA) plan and is often a licensure requirement. However, fidelity checklists designed by original program developers are often lengthy, which makes compliance difficult once programs become widely disseminated in the field. As a case example, we used Stanford’s original Chronic Disease Self-Management Program (CDSMP) fidelity checklist of 157 items to demonstrate heuristic procedures for generating shorter fidelity checklists. Using an expert consensus approach, we sought feedback from active master trainers registered with the Stanford University Patient Education Research Center about which items were most essential to, and also feasible for, assessing fidelity. We conducted three sequential surveys and one expert group-teleconference call. Three versions of the fidelity checklist were created using different statistical and methodological criteria. In a final group-teleconference call with seven national experts, there was unanimous agreement that all three final versions (e.g., a 34-item version, a 20-item version, and a 12-item version) should be made available because the purpose and resources for administering a checklist might vary from one setting to another. This study highlights the methodology used to generate shorter versions of a fidelity checklist, which has potential to inform future QA efforts for this and other evidence-based programs (EBP) for older adults delivered in community settings. With CDSMP and other EBP, it is important to differentiate between program fidelity as mandated by program developers for licensure, and intervention fidelity tools for providing an “at-a-glance” snapshot of the level of compliance to selected program indicators.